Alzheimer's disease-associated peptide Aβ42 mobilizes ER Ca2+ via InsP3R-dependent and -independent mechanisms - Allan, Laura E.; Bultynck, Geert; Luyten, Tomas; Amijee, Hozeefa; Bootman, Martin D.; Roderick, H Llewelyn (Frontiers in Molecular Neuroscience, 2013)
Dysregulation of Ca2+ homeostasis is considered to contribute to the toxic action of the Alzheimer’s Disease (AD) associated Amyloid-β-peptide (Aβ). Ca2+ fluxes across the plasma membrane and release from intracellular stores have both been reported to underlie the Ca2+ fluxes induced by Aβ42. Here, we investigated the contribution of Ca2+ release from the endoplasmic reticulum (ER) to the effects of Aβ42 upon Ca2+ homeostasis and the mechanism by which Aβ42 elicited these effects. Consistent with previous reports, application of soluble oligomeric forms of Aβ42 induced an elevation in intracellular Ca2+. The Aβ42-stimulated Ca2+ signals persisted in the absence of extracellular Ca2+ indicating a significant contribution of Ca2+ release from the ER Ca2+ store to the generation of these signals. Moreover, inositol 1,4,5-trisphosphate (InsP3) signaling contributed to Aβ42-stimulated Ca2+ release. The Ca2+ mobilizing effect of Aβ42 was also observed when applied to permeabilized cells deficient in InsP3 receptors, revealing an additional direct effect of Aβ42 upon the ER, and a mechanism for induction of toxicity by intracellular Aβ42.